Association between an individual dietary index based on the British Food Standard Agency Nutrient Profiling System and asthma symptoms. Issue 1 (19th June 2019) - Andrianasolo, Roland M.; Julia, Chantal; Varraso, Raphaëlle; Egnell, Manon; Touvier, Mathilde; Kesse-Guyot, Emmanuelle; Hercberg, Serge; Galan, Pilar
Abstract: The role of diet in asthma is still debated. In France, a front-of-pack (FOP) nutrition label based on a modified Food Standards Agency Nutrient Profiling System/High Council for Public Health (FSAm-NPS/HCSP) has recently been implemented to help consumers to make healthier food choices during purchase. At the individual level, the FSAm-NPS dietary index (DI) has been shown to reflect the nutritional quality of the diet. The aim of the present study was to investigate the association between the FSAm-NPS DI and the asthma symptom score. In total, 34 323 participants (25 823 women and 8500 men) from the NutriNet-Santé cohort were included. The overall nutritional quality of the diet was assessed using the FSAm-NPS DI. Increasing FSAm-NPS DI reflects decreasing overall diet quality. Asthma was defined by the asthma symptom score (sum of five questions). Negative binomial regression was used to evaluate the association between the FSA-NPS DI and the asthma symptom score. Overall, mean participant's age was 54 ± 14 years, and about 27 % reported at least one asthma symptom. We observed a significant positive association between less healthy diet, as expressed by higher FSAm-NPS DI, and the asthma symptom score. The adjusted OR were 1·27 (95 % CI 1·17, 1·38) among women and 1·31 (95 % CI 1·13, 1·53) among men. Unhealthy food choices, as reflected by a higher FSAm-NPS DI, were associated with greater asthma symptoms. These results reinforce the relevance of public health approach to orient consumers towards healthier food choices by using a clear and easy-to-understand FOP nutrition label based on the FSAm-NPS, such as the Nutri-Score.